2017
DOI: 10.1093/eurpub/ckx048
|View full text |Cite
|
Sign up to set email alerts
|

Migrant women living with HIV in Europe: are they facing inequalities in the prevention of mother-to-child-transmission of HIV?

Abstract: Migrant women were more likely to be diagnosed in late pregnancy but once on ART virological response was good. Good access to antenatal care enables the implementation of PMTCT protocols and optimises both maternal and children health outcomes generally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
2
7
2
1
Order By: Relevance
“…Special multidisciplinary attention should be taken to reach these women as soon as possible after their immigration. Our figures of very late diagnosis were nonetheless substantially lower than in a recent European cohort study [15]. In that study, immigrants were more often diagnosed during pregnancy, diagnosed late in pregnancy and with a lower CD4 count than local women.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Special multidisciplinary attention should be taken to reach these women as soon as possible after their immigration. Our figures of very late diagnosis were nonetheless substantially lower than in a recent European cohort study [15]. In that study, immigrants were more often diagnosed during pregnancy, diagnosed late in pregnancy and with a lower CD4 count than local women.…”
Section: Discussioncontrasting
confidence: 89%
“…diagnosis during pregnancy was 34% if all pregnancies were included; this is still higher than published elsewhere. Favarato et al concluded that pregnancy is an important opportunity to migrant women to learn their HIV status [15]. Our study in a very-low-prevalence setting extends this conclusion also to local women, since both groups were equally undiagnosed before the pregnancy.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Universal antenatal HIV testing, combination antiretroviral therapy (cART) during pregnancy, labour and delivery, neonatal antiretroviral prophylaxis (NP), elective caesarean section (CS) for women without optimal viral suppression near delivery and the avoidance of breast feeding have led to a dramatic decline in the number of perinatally HIV‐infected children: currently, in the USA as well as in Western Europe, mother‐to‐child transmission (MTCT) rates are < 1% . However, there remain missed opportunities for prevention of MTCT (PMTCT) in these settings, including late diagnosis of HIV infection in pregnant women and failure to control viral replication during pregnancy as a consequence of inadequate or lack of cART, and low adherence .…”
Section: Introductionmentioning
confidence: 99%
“…B. auch aus Finnland [12], Spanien [13], Italien [14], Frankreich [3,15] und dem Vereinigten Königreich [4,[16][17][18] berichtet. Eine verbesserte Testung in der Schwangerschaft wird auch aus Spanien und Italien berichtet, und Zugangsprobleme zur Gesundheitsversorgung für Migrantinnen sind eine Problematik, die Deutschland mit vielen anderen europäischen Ländern teilt [19][20][21].…”
Section: Introductionunclassified